PENGUATAN NILAI-NILAI PANCASILA DAN KEBANGSAAN KEPADA PESERTA DIDIK PADA LAYANAN BIMBINGAN DAN KONSELING DI SEKOLAH - Riswanto, Dody (Universitas Negeri Manado, 2019)
Pancasila is a state philosophy that must be adhered to by all Indonesians, Counselors as Guidance and Counseling Teachers must provide reinforcement of Pancasila and Nationality values to all students in the school. The research method used is qualitative with data collection techniques, namely interviews, observation, documentation studies and data triangulation. Strengthening the values of Pancasila and Nationalism for students by counselors can instill a high spirit of nationalism and love for the country, and from this high spirit of nationalism comes quality human resources for the development of the nation and state.Keywords: Strengthening; Values; Pancasila; Nationality; Students